CULTURE OF ENGLISH-SPEAKING COUNTRIES - Musabekova Mubinaxon, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
This thesis explores the cultural features of major English-speaking countries — the United States, the United Kingdom, Canada, and Australia. It discusses each nation's unique traditions, values, and social behaviors, as well as the role of the English language in their daily lives. Moreover, it highlights the global influence of these cultures and their significance in understanding the English language from a broader, more meaningful perspective.